2017
DOI: 10.3390/su9091526
|View full text |Cite
|
Sign up to set email alerts
|

Types, Indications and Impact Evaluation of Sand and Dust Storms Trajectories in the Arabian Gulf

Abstract: Dust is a common weather phenomenon in the Arabian Gulf, which has severely affected economy and health. Sand and dust storms (SDS) trajectories in the Arabian Gulf were temporally and spatially monitored from March 2000 to March 2017. Eight major SDS trajectories were detected from satellite images. The dust storms trajectories were categorized according to shape and size into three main types with 12 subtypes in the region. The annual transported dust amount into the Arabian Gulf was estimated by 89.1 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…During winter and summer months (monsoon periods), SDS appears with the least frequency, with some exceptional cases however present during February and June. For the entire time period of this study, Kuwait is found to be affected by SDS with a mean annual frequency of 19.4 days/year, ranging from 35 days/year (in 2008) to 13 days/year (in 2017), in agreement with recent studies performed with satellite images and in-situ measurements (i.e., dust traps) [44]. The lasting time period of these events, varies from 1 up to 5 consequent days, with the latter appearing during the months of May and June.…”
Section: Aod Levels and Seasonal Variationsupporting
confidence: 91%
“…During winter and summer months (monsoon periods), SDS appears with the least frequency, with some exceptional cases however present during February and June. For the entire time period of this study, Kuwait is found to be affected by SDS with a mean annual frequency of 19.4 days/year, ranging from 35 days/year (in 2008) to 13 days/year (in 2017), in agreement with recent studies performed with satellite images and in-situ measurements (i.e., dust traps) [44]. The lasting time period of these events, varies from 1 up to 5 consequent days, with the latter appearing during the months of May and June.…”
Section: Aod Levels and Seasonal Variationsupporting
confidence: 91%
“…This study also revealed that dust storms, suspended dust, rising dust and PM 10 followed a similar pattern throughout the studied period with high peaks during summer months, specifically in June, and lower during winter months; this finding confirms the robust link between dust storm events and ambient air PM 10 levels and is in agreement with other studies in similar arid conditions [6,29,43,44]. Increased PM 10 concentrations during the summer can be associated with the Middle Eastern dust storms from the arid lands of Iraq, Jordan, and Saudi Arabia which are the particular sources of dust events coming to Kuwait from the Northwest [2,29,45].…”
Section: Discussionsupporting
confidence: 79%
“…The northern region of the Arabian region is characterized by complex dust storm trajectories where they pass through the western desert of Syria and Iraq toward the Mesopotamian flood plain reaching the northeastern region of the peninsula into Kuwait at a dust fallout rate of 61.4 tons per km 2 per year, where fallen dust compromises 37% of sand particles [2,3]. A particular feature of blown dust is its extreme particulate matter intensity that increases the ambient air dust concentrations for several days.…”
Section: Introductionmentioning
confidence: 99%
“…The observed temporal trends might be a result of large-scale land-use change dynamics within Saudi Arabia (e.g., urbanization and variability in vegetation coverage) [74,75], as well as in neighboring military conflict areas, such as Syria and Iraq, where a widespread abandonment of fields resulted in an enhanced dust erodibility of the soil [76]. As these regions are located on the most important dust trajectories reaching the northeastern part of the Arabian Peninsula [77], it is likely to result in a locally increased dust supply. Furthermore, climate change might also have an impact on the frequency of dust storms, as drier and hotter conditions may reduce the overall vegetation coverage and, therefore, intensify the desertification process [38,78].…”
Section: Large-scale Trends and Driversmentioning
confidence: 99%